Ultraviolet Protection by Fabric Engineering. (3rd April 2013) - Singh, Mukesh Kumar; Singh, Annika
Abstract : Background . The increasing emission of greenhouse gases has evoked the human being to save the ozone layer and minimize the risk of ultraviolet radiation (UVR). Various fabric structures have been explored to achieve desired ultraviolet protection factor (UPF) in various situations. Objective . In this study, the effect of various filament configurations like twisted, flat, intermingled, and textured in multifilament yarns on fabric in different combinations is assessed in order to engineer a fabric of better ultraviolet protection factor (UPF). Methods . In order to engineer a fabric having optimum UV protection with sufficient comfort level in multifilament woven fabrics, four different yarn configurations, intermingled, textured, twisted, and flat, were used to develop twelve different fabric samples. The most UV absorbing and most demanding fibre polyethylene terephthalate (PET) was considered in different filament configuration. Results . The combinations of intermingled warp with flat, intermingled, and textured weft provided excellent UVR protection comparatively at about 22.5 mg/cm 2 fabric areal density. The presence of twisted yarn reduced the UV protection due to enhanced openness in fabric structure. Conclusion . The appropriate combination of warp and weft threads of different configuration should be selected judiciously in order to extract maximum UV protection and wear comfort attributes in multifilament woven PET fabrics.